Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.2174/2211352519666210217100944
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Anti-Candida Activity of Artemisia herba alba asso and Citrus aurantium Extracts Formulated in Different Ointments

Abstract: Background: Today, people around the world have resorted to herbal medicine, due to the increase in antibiotic resistance and the side effects of synthetic drugs. Methods: Our research focused on the in vivo antifungal activity of three ointments formulated on the basis of methanolic extract of Citrus aurantium peel, ethanolic extract of the aerial part of Artemisia herba alba asso, and essential oil of Artemisia herba alba asso. Wistar rats were made immunosuppressed by Dexamethazone and Tetracycline. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Citrus fruits have reportedly been found to have immunostimulatory, anti-inflammatory, antimicrobial, and antioxidant properties 64 66 . It had considerable antibacterial efficacy against S. aureus and Candida-skin-infections, including-oral-and-vaginal-candidiasis 65 , 67 70 . Fascinating studies have shown that Citrus oil may change the way that inflammatory responses are expressed, suppressing pro-inflammatory cytokines and enhancing skin's defensive barriers 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Citrus fruits have reportedly been found to have immunostimulatory, anti-inflammatory, antimicrobial, and antioxidant properties 64 66 . It had considerable antibacterial efficacy against S. aureus and Candida-skin-infections, including-oral-and-vaginal-candidiasis 65 , 67 70 . Fascinating studies have shown that Citrus oil may change the way that inflammatory responses are expressed, suppressing pro-inflammatory cytokines and enhancing skin's defensive barriers 71 .…”
Section: Discussionmentioning
confidence: 99%